Treatment of pediatric severe acute myopericarditis with anakinra: a case report and literature review - Licciardi, Francesco; Fornari, Federico; Ferroni, Francesca; Covizzi, Carlotta; Riggi, Chiara; Montin, Davide (Frontiers in Pediatrics, 2025)
Acute myocarditis (AM) is an inflammation of the myocardium with a rapid onset of typically <1 month. The use of anakinra (ANK) for treating inflammatory AM in adults has been recently described; however, while some reports are promising, its efficacy remains debated. Here, we present a case of severe AM with concomitant systemic symptoms [fever, elevated C-reactive protein (CRP)] in a pediatric patient who was successfully treated with high-dose ANK. A literature review of similar published cases is also presented. A 14-year-old boy was admitted for AM with concomitant pericarditis. At disease onset, the patient presented with high fever and elevated CRP (163 mg/L) and troponin I (14,816 ng/L). Treatment with ibuprofen (30 mg/kg/day), intravenous immunoglobulin (80 g in 24 h), and colchicine (0.5 mg per day) were initiated without benefit and with further worsening of contractile function [Ejection Fraction (EF) 26%]. Consequently, inotropic support and intravenous methylprednisolone were started, leading to a partial improvement of EF (45%). Due to the inability to reduce inotropic support, a rescue treatment with ANK (7 mg/kg/day) in continuous intravenous infusion was started, resulting in progressive improvement and normalization of left ventricular systolic function. Our literature review identified five case reports of pediatric AM successfully treated with ANK. Most cases presented elevated inflammatory markers (ferritin and CRP) and/or concomitant pericarditis. We conclude that ANK, especially at high doses, may be useful for treating severe pediatric AM, particularly when associated with severe inflammation and/or pericarditis.